Removal of Bisphenola A applying sonophotocatalysis / Sharmini Sunasee - Sharmini, Sunasee (2018)
Bisphenol A (BPA), a chemical compound that exhibits endocrine disrupting action can be found in aquatic systems. Its complete elimination has been demanded due to its high toxic effects. Initially, the BPA removal by sonophotocatalysis coupled with titanium dioxide (TiO2, P25) was conducted with various batch tests using energy-based advanced oxidation combining ultrasound (US) and ultraviolet (UV). The kinetics of BPA removal were systematically evaluated with not only various operational parameters such as US frequency and power, mechanical stirring speed, and temperature, but also comparison between sole and coupled system under the optimum condition of US (35 kHz, 50W, 300 rpm stirring speed and 20oC). The combination of US/UV/P25 was the highest BPA removal rate. The removal of BPA was investigated to identify BPA by-products and intermediates by use of a high-performance liquid chromatography mass spectrometry (HPLC-MS) and five main intermediates were formed during the sonophotocatalytic degradation. They were monohydroxylated bisphenol A, 4-isopropenylphenol, monohydroxylated 4-isopropenylphenol, dihydroxylated bisphenol A, and 4-hydroxyacetophenone. This study was further investigated to operate energy-saving sonophotocatalysis process and find out the effectiveness of sonophotocatalytic with the presence of nano-structured graphitic carbon nitride (GCN) as environment-friendly sonophotocatalyst. The material was prepared through a facile pyrolysis by using urea as a precursor and it displayed good visible-light-driven photocatalytic performance. There is no any significant effect on pH 4-8 of BPA solution. Therefore, the entire test was carried out at pH 7. The sonophotocatalytic performance was the highest BPA removal rate compared to other Advance Oxidation Process (AOP) application. There were five intermediates, monohydroxylated BPA, dihydroxylated BPA, 4-hydroxyacetophenone, 4- isopropenylphenol and 4-hydroxybenzaldehyde identified in the presence of GCN under sonophotocatalysis process. Reusability test of GCN was carried out for five times and resulting a good capability of reuse up to third cycle. The advantages of using GCN as sonophotoctalyst were energy save and environment-friendly material because a very good visible light driven and synthesised by non-toxic starting material and the capability of reuse.